Reduced striatal dopamine transporter density associated with working memory deficits in opioid-dependent male subjects: a SPECT study - Liang, Chih-Sung; Ho, Pei-Shen; Yen, Che-Hung; Yeh, Yi-Wei; Kuo, Shin-Chang; Huang, Chang-Chih; Chen, Chun-Yen; Shih, Mei-Chen; Ma, Kuo-Hsing; Huang, San-Yuan (Addiction biology, 2016)
Research on the effects of repeated opioid use on striatal dopamine transporters has yielded inconsistent results, possibly confounded by a history of methamphetamine or methadone exposure in opioid‐dependent individuals. Previous studies have shown that striatal dopamine transporter density is positively correlated with the cognitive performance of healthy volunteers. This study aimed to investigate changes in striatal dopamine transporter density and their functional significance in opioid‐dependent individuals. Single‐photon emission computed tomography with [99mTc]TRODAT‐1 as a ligand was used to measure striatal dopamine transporter levels in 20 opioid‐dependent individuals and 20 age‐ and sex‐matched healthy controls. Opioid‐dependent individuals had no history of methamphetamine or methadone use. The Wisconsin Card Sorting Test (WCST) was performed to assess neurocognitive function. We found that compared with healthy controls, opioid‐dependent individuals showed a significant reduction in striatal dopamine transporter density. They also showed poorer performance on the WCST in terms of the trials administered, total errors, perseverative responses, perseverative errors, and non‐perseverative errors. Striatal dopamine transporter levels negatively correlated with non‐perseverative errors not only in opioid‐dependent individuals but also in healthy controls. These findings suggest that in human, repeated opioid exposure reduces striatal dopamine transporter density, which can be associated with non‐perseverative errors. Non‐perseverative errors may be one of the more sensitive parameters in WCST to identify working memory deficits associated with striatal dopamine transporter reduction. Moreover, we suggest that whether opioid‐associated neurotoxicity is reversible depends on the brain region.